English Faktor Penentu Kesediaan Rumah Tangga Menggunakan Biodiesel: Universitas Pertamina - Nanda Rembulan Nurdianto; Gina Kultsum; Eka Puspitawati; Andika Pambudi; Rico Ricardo; Feriansyah (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2023)
The subsidy policy of diesel in Indonesia is considered inefficient since it results an increase in the burden on the Government Budget (APBN), distribution process is not well targeted and encourages wastage of consumption. Then, in 2014 the Indonesia government decided to cut diesel subsidies and began marketing alternative solar products, namely biodiesel, as an effort to ensure energy sustainability. Therefore, this study aims to analyze the determinant that influences household’s willingness to use biodiesel using quantitative methods. The results show that there are three variables having a significant effect on the willingness to use biodiesel, namely age, occupation, and knowledge.